Monolayer black phosphorus by sequential wet-chemical surface oxidation - Wild, Stefan; Lloret, Vicent; Vega-Mayoral, Victor; Vella, Daniele; Nuin, Edurne; Siebert, Martin; Kolesnik-Gray, Maria; Loeffler, Mario; Mayrhofer, Karl J. J.; Gadermaier, Christoph; Krstic, Vojislav; Hauke, Frank; et al. (RSC Advances, 2019)
We report a straightforward chemical methodology for controlling the thickness of black phosphorus flakes down to the monolayer limit by layer-by-layer oxidation and thinning, using water as solubilizing agent. Moreover, the oxidation process can be stopped at will by two different passivation procedures, namely the non-covalent functionalization with perylene diimide chromophores, which prevents the photooxidation, or by using a protective ionic liquid layer. The obtained flakes preserve their electronic properties as demonstrated by fabricating a BP field-effect transistor (FET). This work paves the way for the preparation of BP devices with controlled thickness.
CRIS-Team WoS Importer:2019-02-21